The effect of friction behavior on the migration of metal elements from stainless-steel articles for food contact - Jingjing PAN; Zhaoping LIU; Qian LU; Yu ZONG; Dan LI; Jianguo ZHENG; Haixia SUI; Huaining ZHONG (Zhongguo shipin weisheng zazhi, 2020)
Objective To evaluate the effect of friction behavior on migration levels of metal elements from stainless-steel articles for food contact. Methods The migration levels of metal elements from used and new stainless-steel articles were compared according to GB 4806.9-2016 and Council of Europe Resolution CM/Res (2013) 9. The migration conditions were boiling in 4% acetic acid for 30 min followed by at room temperature for 24 h and soaking in 5 g/L citric acid at 100 ℃ for 2 h, respectively. Meanwhile, the impact of dynamic friction on migration were investigated on new stainless-steel articles, where the friction method were referred to the GB/T 32095.2-2015 standard. Migration of metal elements complied with the corresponding standard. Results Based on the European standard, migration of lead in the first migration test was above limit of quantitation (LOQ) in all five used stainless-steel articles after friction, but none in new ones. The quantification rate of chromium in the first migration test in 80% (4/5) of used stainless-steel articles were above LOQ after friction by GB 4806.9-2016 standard while were 20% (1/5) in new ones. The migration level of Cr was higher by GB 4806.9-2016 standard than by European resolution in single dynamic friction study. Results from the dynamic friction experiments indicated that the migration of Cr and Ni reached equilibrium after 3 times of friction. Conclusion The migration condition in GB 4806.9-2016 standard had stronger leaching ability for Cr from stainless-steel articles than that in European resolution. Friction behavior promoted corrosion and metal element migration of stainless steel. Long-term used stainless-steel products had higher lead and chromium migration than new products, but without safety risks.